"HASSLES" in Caring a Child Suffering from Anorectal Malformation with Colostomy: A Phenomenological Study. Issue 1 (January 2022) - Sugesh, A.; Kaur, Sukhwinder; Sharma, Sunita; Samujh, Ram
Introduction: Anorectal malformations (ARM) are the birth defects, in which anus and rectum mature inappropriately, which include a wide spectrum of diseases ranging from simple imperforate anus to cloaca. Children with ARM and the caregivers have to undergo a lot of struggles/hassles to maintain a near-normal daily living. The impact of the disease is profound, as it affects the child's entire life and the whole family dynamics. Objective: To explore the hassles of caregivers of children suffering from ARM and having a colostomy. Materials and Methods: A phenomenological research were conducted. A purposive sampling technique was used to conduct in-depth interview of caregivers of children suffering from ARM, who met the inclusion criteria. In-depth interviews were conducted telephonically using an interview guide. Fifteen caregivers were interviewed and all the interviews were recorded and verbatims were prepared. Analysis of data was done by Colaizzi's analysis steps and formulated themes and subthemes. Result: The study results showed the difficulty of caregivers in caring for a child suffering from ARM and colostomy. The theme emerged was "Hassles in caring for the child with ARM and colostomy." The subthemes were balancing home management and child care, lack of support system, lack of specialized training, fear in doing care, problems in feeding, readmissions because of health issues and troubles in hospital stay. Conclusion: The caregivers face a lot of hassles while caring for a child with ARM and colostomy. The study revealed the difficulties experienced by the caregivers in caring for the child suffering from ARM and having colostomy. The study will be helpful for students, nurses, doctors, and other health care providers to identify the various problems faced by caregivers and to take certain initiatives to lessen their strain of caregiving process.